Window decompression surgery for a large radicular cyst in a 7-year-old patient: A case report - Guan-jie Song; Lu Wang; Li-rong Gao (SAGE Open Medical Case Reports)
Radicular cysts are rarely present in the primary dentition because of the distinct biological cycle of primary teeth. Cyst formation in children may cause bony expansion and resorption, malposition, delayed eruption, enamel defects, or damage to the developing permanent successors. Various treatment modalities for the management of radicular cysts have been reported in the literature. In this case, the preferred treatment approach is window decompression surgery (WDS) combined with gap retainers. Long-term follow-up revealed good healing of the bony lesion. The present case involved an abnormally large radicular cyst in a 7-year-old girl. After surgery, WDS was performed, and a gap retainer was provided. At the 9-month follow-up, the radicular cyst had healed and the impacted tooth had erupted. The aim of this study was to explore the clinical effectiveness of WDS for impacted teeth within root radicular cysts.